2004
DOI: 10.1038/sj.pcan.4500726
|View full text |Cite
|
Sign up to set email alerts
|

Improved urinary continence after radical retropubic prostatectomy with preparation of a long, partially intraprostatic portion of the membraneous urethra: an analysis of 1013 consecutive cases

Abstract: Purpose: To improve the rate of full continence in our patients, we performed, since June 1997, a careful preparation of the distally intraprostatic part of the membranous urethra to obtain a long urethral stump for the vesicourethral anastomosis. Patients and methods: In all, 610 patients without (group 1) and 403 patients with (group 2) a long intraprostatic stump of the urethra were asked by a selfadministered questionnaire about their continence status. The rate of positive surgical margins were compared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 25 publications
1
28
1
1
Order By: Relevance
“…As the preoperative parameters are given, it seems to be logical that improving postoperative continence might be triggered by the preservation of a longer urethral stump besides better striated sphincteric function. Van Randenborgh et al [21] proved that the preparation of a long, partially intraprostatic portion of the membranous urethra available for vesicourethral anastomosis leads to a statistically highly significant improvement of continence and earlier continence recovery. Coakley et al [23] used endorectal MRI to measure preoperative membranous urethral length and demonstrated that in case the membranous urethral length is longer than 12 mm, the postoperative continence could be gained more rapidly and the rate of complete continence is also higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the preoperative parameters are given, it seems to be logical that improving postoperative continence might be triggered by the preservation of a longer urethral stump besides better striated sphincteric function. Van Randenborgh et al [21] proved that the preparation of a long, partially intraprostatic portion of the membranous urethra available for vesicourethral anastomosis leads to a statistically highly significant improvement of continence and earlier continence recovery. Coakley et al [23] used endorectal MRI to measure preoperative membranous urethral length and demonstrated that in case the membranous urethral length is longer than 12 mm, the postoperative continence could be gained more rapidly and the rate of complete continence is also higher.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies dealing with postprostatectomy incontinence focused on urodynamic factors being responsible for incontinence [5][6][7][8] , whereas others tried to analyze the impact of the pre-and perioperative factors ( table 1 ) on urinary incontinence [2][3][4][9][10][11][12][13][14][15][16][17] . Some of the authors showed no association between the above-mentioned factors and postoperative incontinence [2, 11-13, 15, 17] , while others believed that older age, lack of a nerve-sparing technique, presence of anastomotic stricture, bladder neck resection and creating vesicourethral anastomosis without a long, partially intraprostatic portion of the urethra could be responsible for incontinence or at least represent risk factors delaying continence [1,3,4,9,10,14,16,[18][19][20][21] . Univariate analysis was used in the majority of these studies in order to determine the risk factors related to incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…For example, preoperative MRI has demonstrated that longer membranous urethral length was associated with decreased time to urinary control after surgery [ 65,66 ] . This has led some to preserve an intraprostatic portion of the membranous urethra to hasten urinary recovery [ 67 ] . Finally, surgery in the setting of prior radiation therapy (i.e., salvage prostatectomy) results in worse urinary incontinence than in standard settings due to postradiation tissue changes [ 68 ] .…”
Section: Surgery and Urinary Incontinencementioning
confidence: 99%
“…The striated sphincter is functional from the prostate apex to the bulb, whereas the internal component of the distal sphincter mechanism extends to the verumontanum 31) . Maximum preservation of not only striated sphincter but also the intraprostatic portion of the membranous urethra leads to a highly significant improvement of full continence and earlier continence 32) . The most critical point to maintaining maximal urethral length without compromising apical margin status is to identify the junction between the prostatic apex and the proximal urethra precisely.…”
Section: ) Preservation Of Urethral Lengthmentioning
confidence: 99%